ANALISIS PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI PADA STAF AKUNTANSI DAN KEUANGAN - Anugerah Putri Suciati; Christina Dwi Astuti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
Human resources in an organization are a crucial aspect that determined the effectiveness of it. The implication is that an organization needs to always investing by making the human resources, in this case is the staff to be satisfaction while working. On the other side, the staff commitment in organization is an important thing and the companies have to pay serious attention for it. From the statement above, question like is there any impact of job satisfaction to organizational commitment If demographic became the characteristic that affect internal, external, and general job satisfaction, and is there any impact of job satisfaction to commitment organizational if three components as the indicator of commitment organizational; policy, compensatio4 and working condition appears. Data is gotten by giving 150 questionnaires to accounting and financial staff in manufacturing companies in Bekasi and Jakarta area. The technique to take samples is using a convenience sampling method. This research using Structural Equation Model—SEM for hypothesis test that shows there is an impact from several demographic factors to intrinsic, extrinsic, and general job satisfaction. And there is an impact of job satisfaction to organizational commitment f or company policy, compensation and working condition indicators